Residual axial capacity of reinforced concrete columns with simulated blast damage - Li, Bing (2012)
Two specimen series [limited seismic (LS) and nonseismic (NS)] were subjected to quasistatic loadings to evaluate the residual axial capacity of blast-damaged reinforced concrete (RC) columns. A validated numerical model was used to predict the residual lateral deflection of RC columns subjected to an explosive attack. Three hydraulic actuators were installed horizontally to reproduce the target residual lateral deflection as predicted through this numerical model. Another two hydraulic actuators were installed vertically to apply the axial load and measure the residual axial capacity of the damaged columns. The effects of parameters such as axial loading and the transverse reinforcement ratio are investigated through this study. The results obtained from the experimental study showed the improved performance that LS detailing provided to RC columns to resist blast or lateral loads. This subsequently led columns detailed with a higher transverse reinforcement ratio to have an increased residual axial capacity when laterally damaged, as compared with the NS detailed specimens. Axial load (service load) on the columns was also found to affect the residual deflection profile and residual axial capacity of the columns after the specified blast event. The validity range of a previously published function to determine blast-damaged residual axial capacity of RC columns is refined through the results obtained.